China's Miracle in Foreign Trade - Yu, Miaojie (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book mainly focuses on the miracle of China's foreign trade in the past 40 years from five perspectives: first, it briefly reviews the import substitution strategy China adopted before its opening-up; second, it analyzes the export-oriented strategy that contributes a lot to China's economic growth since 1980s; third, it discusses the impacts of trade liberalization and China's participation in WTO on Chinese firms; forth, it addresses the deepening opening-up in the context of global financial crisis; last, it provides policy advice on China's newly conducted all-around opening-up strategy. By dividing China's opening-up into five stages, this book offers a comprehensive discussion to understand and analyze the reason, performance and challenge of China's economic growth from the perspective of foreign trade.
Part 1. Overview -- Chapter 1.China's opening-up policies: achievements and prospects -- Part 2. Import substitution & trade protection -- Chapter 2. The economics of price scissors: an empirical investigation for China -- Chapter 3.Measuring the impact of trade protection on industrial production size.-Part 3. Export-led & firm productivity -- Chapter 4. China's processing trade: A firm-level analysis -- Chapter 5. Estimating productivity using Chinese data: methods, challenges and results -- Chapter 6. Place-based industrial policy and firm productivity -- Chapter 7. Managerial efficiency and product decision: evidence from Chinese firms -- Part 4. Trade liberalization strategy -- Chapter 8. Measured skill Premia and input trade liberalization: evidence from Chinese firms -- Chapter 9.Input trade liberalization and import switching: evidence from Chinese firms -- Part 5. All-round opening-up strategy -- Chapter 10. Worker training, firm productivity, and trade liberalization: evidence from Chinese firms -- Chapter 11. China's free trade ports: Effective action against the threat of de-globalization -- Chapter 12. Forty years of opening up has greatly benefited China's foreign trade -- References.
Keywords: Economic history; Economic development; Economy-wide Country Studies; Development Studies